Clinical events and echocardiographic lesion progression rate in subjects with mild or moderate aortic regurgitation - Badiani, Sveeta (Echo Res Pract, 2017)
BACKGROUND: The rate of progression of aortic regurgitation (AR) is not well described. Current guidelines state that asymptomatic patients with mild AR should be followed up every 3–5 years and 1–2 yearly for moderate AR. This study describes the lesion and clinical based progression of mild and moderate AR in a population of patients undergoing systematic follow-up. METHODS AND RESULTS: 341 patients with either mild or moderate AR were included. The rates of clinical events (death, aortic valve replacement and cardiac hospitalization) and progression of AR are reported. 341 patients were included; mean age was 71.1 years (IQR 66–80 years) and the median follow-up period was 4.6 (IQR 2–6.7) years. 292 patients did not have any events during follow-up. 3 patients required aortic valve replacement (2 of these due to severe aortic stenosis and 1 due to severe mitral regurgitation and co-existent moderate AR). 44 patients required cardiac hospitalization. 9 patients died during follow-up and 35 patients (10%) showed a progression of AR during follow-up with an average time of 4.0 ± 2.6 years. 8 patients (2.3% of the total) progressed to severe AR. Patients with mixed valvular pathology showed a greater increase in AR progression (27 (15%) vs 8 (5%); P = 0.004). CONCLUSIONS: Over medium term systematic follow-up progression and clinical events in patients with AR is rare, regardless of etiology. Patients who suffered from AR as an isolated valve pathology were less likely to show AR progression over time.